Venn Diagram Strategy in Improving Students Speaking Skills at one of the Public High Schools in Batam - Hilarius Raditya Priambada Purba; Abdul Aziz Satrio (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to find out how well the Venn diagram method helps students develop their speaking abilities. Classroom action research is the approach that will be utilized to measure student learning or accomplishment as a result of an intervention; pre-tests and post-tests are frequently employed in classroom action research. The study results showed that, following the implementation of the Venn diagram strategy cycle, the participants in the classroom action research considerably improved. The results show that the Venn diagram concept is an effective strategy for enhancing speaking abilities. Keywords: Brain Storming, Classroom Action Research, Speaking skills, Students Speaking Ability, Venn Diagram Strategy